Interspecific variations of photochemical properties in a xerotherm grassland community - Veres, Szilvia (Acta Biologica Szegediensis, 2002)
In this work the role of xanthophyll cycle an d its relation to the photosynthetic activity in the dominant species of a semiarid sandy grassland community (Potentillo-Festucetum pseudovinae) were studied during the stressful summer period . The total amount of xanthophyll cycle pigments (violaxanthin, anteraxanthin, zeaxanthin) related to total chlorophyll content (VAZ pool) showed considerable interspecific alterations and it was 2-3 times larger in the summer period than in spring. The changes in the xanthophyll cycle , the potential (FyFm) and actual photochemical efficiency (AF/Fm) of PSII, as well as, the results of parallel measurements on their daily dynamics show that zeaxanthin has a major role in the photoinhibition in the photosynthetic apparatus during the summer stress on sandy grassland species. In July, the decrease s of F/F m was accompanied with increases of NPQ at the 100-120% extentt depending on the species.